Ekstrak Kulit Pisang (Musa Paradisiaca) Sebagai Green Corrosion Inhibitor Pada Baja Karbon Rendah Dalam Larutan Hcl 0.5 M Dan 1 M - Sry Utami Pardede; Komalasari Komalasari; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Corrosion has been identified as one of the major problems in the chemical industry, especially in the pipeline’s system. The inhibitor is the most effective way to protect the metal against corrosion. The natural corrosion inhibitor is chosen as an alternative because it’s safe, widely available, low cost, biodegradable and environmentally friendly. This study aims to know the corrosion rate and the inhibition efficiency of banana peel extract for low carbon steel. Banana peel extract was obtained by soxhlet extraction using ethanol-water as the solvent. Corrosion rate were determined by using the weight loss method. Low carbon steel was immersed in HCl 0.5 m and 1 M with and without banana peel extract 0 g/L, 0.5 g/L, 1 g/L, 1.5 g/L and 2 g/L by immersion time 24 h. The result showed that corrosion rate decreases on increasing of concentration of the extract and increases the inhibition efficiency. The maximum efficiency was obtaining at 2 g/L of corrosion inhibitor in HCl 0.5 M with inhibition efficiency 82.19%.Keywords: banana peel extract, corrosion, HCl, inhibitor, low carbon steel